Exploring the impact of defect energy levels in CdTe/Si dual-junction solar cells using wxAMPS - Isah M.; Doroody C.; Rahman K.S.; Rahman M.N.A.; Goje A.A.; Soudagar M.E.M.; Kiong T.S.; Mubarak N.M.; Zuhdi A.W.M. (Nature Research, 2025)
A numerical analysis of a CdTe/Si dual-junction solar cell in terms of defect density introduced at various defect energy levels in the absorber layer is provided. The impact of defect concentration is analyzed against the thickness of the CdTe layer, and variation of the top and bottom cell bandgaps is studied. The results show that CdTe thin film with defects density between 1014 and 1015cm?3 is acceptable for the top cell of the designed dual-junction solar cell. The variations of the defect concentrations against the thickness of the CdTe layer indicate that the open circuit voltage, short circuit current density, and efficiency (?) are more affected by the defect density at higher CdTe thickness. In contrast, the Fill factor is mainly affected by the defect density, regardless of the thin film?s thickness. An acceptable defect density of up to 1015cm?3 at a CdTe thickness of 300nm was obtained from this work. The bandgap variation shows optimal results for a CdTe with bandgaps ranging from 1.45 to 1.7eV in tandem with a Si bandgap of about 1.1eV. This study highlights the significance of tailoring defect density at different energy levels to realize viable CdTe/Si dual junction tandem solar cells. It also demonstrates how the impact of defect concentration changes with the thickness of the solar cell absorber layer. ? The Author(s) 2024.